Implikasi Pemberlakuan Sistem Perbankan Ganda Terhadap Penerapan Norma Hukum Islam Di Dalam Perbankan Syariah Di Indonesia - Agus Rojak Samsudin; Hadiat Hadiat (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2024)
The Financial System is regulated in Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK). Dual banking system is the implementation of the banking system simultaneously, namely conventional banks and Islamic banks simultaneously. The implementation of the Dual banking system is based on Law No. 7 of 1992 concerning Banking, in which it regulates shortcuts about the system and is perfected by Law No. 10 of 1998. As a result of the implementation of the "dual banking system model", legal problems arise, especially in the intermediation function of Islamic banks as financial institutions that have differences in the variation of fund distribution to the public, with the intermediation function of conventional banks as financial institutions that can only channel funds to the public in the form of credit. The implications of implementing this dual banking system are the gateway to implementing Islamic economic legal norms in every Islamic bank product and business. To ensure compliance with sharia principles, DSN MUI issues fatwas. The MUI DSN fatwa was then formalized through PBI and POJKut selanjutnya diformalkan melalui PBI maupun POJK.